BEYOND EPISTEMOLOGICAL RELIGIOUS TRUTH A REFLECTION OF THE OTHER OUTSIDE “TRUE-FALSE” CATEGORY - Yohanes Slamet Purwadi (Jurnal Kawistara, 2012)
The aim of this paper is to investigate the problematic and dynamic of ‘religious truth’, put into the context of religious freedom in today’s Indonesia. Generally speaking, the dominant discourse of religious truth in Indonesia is heavily determined by epistemological knowledge and understanding. In everyday language, through which this knowledge is produced and distributed, some epistemological categories, such as ‘deviant-believer’, ‘true- false’, and even ‘blasphemy’- are commonly applied. Here, in the problem lies these categorizations might open up possibility for the xation of ‘truth’, which in turn, inclines to subordinate what generically refer to as ‘the other’Seeking    an    alternative,    this    paper    attemptsto develop more favorable and inclusive religious understanding, which indebted to the mode of existential religious understanding including linguistic model of translation. Employing Ricouerian’s hermeneutics, this mode of existential understanding offers valuable critique to the monopoly and orthodoxy of religious truth. Moving further, it promotes the others as an interpretative horizon and a ‘circling way’, through which we enrich our religious understanding, as well as self-understanding.